2019
DOI: 10.1136/annrheumdis-2018-214930
|View full text |Cite
|
Sign up to set email alerts
|

Altered DNA methylation in children born to mothers with rheumatoid arthritis during pregnancy

Abstract: ObjectivesThe main objective of this study was to determine whether the DNA methylation profile of children born to mothers with rheumatoid arthritis (RA) is different from that of children born to mothers from the general population. In addition, we aimed to determine whether any differences in methylation are associated with maternal RA disease activity or medication use during pregnancy.MethodsFor this study, genome-wide DNA methylation was measured at cytosine-phosphate-guanine (CpG) sites, using the Infin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…In this respect, it has been shown that RA during pregnancy, either related to the disease itself, disease activity or medication, is associated with marked epigenetic changes in the offspring. 25 In addition, in several populations of healthy mothers and their children, it has been shown that DNA-methylation in the newborn is associated with birth weight. 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this respect, it has been shown that RA during pregnancy, either related to the disease itself, disease activity or medication, is associated with marked epigenetic changes in the offspring. 25 In addition, in several populations of healthy mothers and their children, it has been shown that DNA-methylation in the newborn is associated with birth weight. 26 …”
Section: Discussionmentioning
confidence: 99%
“…An alternative, but not mutually exclusive, hypothesis could be that treatment with TNFi during pregnancy is able to induce epigenetic changes in the fetus, which positively influence fetal growth. In this respect, it has been shown that RA during pregnancy, either related to the disease itself, disease activity or medication, is associated with marked epigenetic changes in the offspring 25. In addition, in several populations of healthy mothers and their children, it has been shown that DNA-methylation in the newborn is associated with birth weight 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be speculated that DNA methylation could influence the long-term outcome of these children and open new interesting scenarios. It remains unknown whether the identified associations are causal, and if so, whether they are caused by either the disease or the treatment during pregnancy ( Ince-Askan et al, 2019b ).…”
Section: The Long-term Outcome Of Children Born To Women With Inflammmentioning
confidence: 99%
“…CT is to apply X-rays or c-rays to scan a certain part of the human body together with a highly sensitive detector, which is featured with fast scanning time and clear scanned images [5]. In recent years, CT images have been extensively used in the field of medical clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%